2021
DOI: 10.1038/s41598-021-89230-3
|View full text |Cite
|
Sign up to set email alerts
|

Development of P301S tau seeded organotypic hippocampal slice cultures to study potential therapeutics

Abstract: Intracellular tau inclusions are a pathological hallmark of Alzheimer's disease, progressive supranuclear palsy, corticobasal degeneration and other sporadic neurodegenerative tauopathies. Recent in vitro and in vivo studies have shown that tau aggregates may spread to neighbouring cells and functionally connected brain regions, where they can seed further tau aggregation. This process is referred to as tau propagation. Here we describe an ex vivo system using organotypic hippocampal slice cultures (OHCs) whic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 38 publications
0
3
0
Order By: Relevance
“…Moreover, slice cultures have been employed to explore the prion-like propagation of Aβ and tau [ 42 , 43 , 44 ]. Recently, our group has explored the spreading of Aβ and α-Syn using organotypic coronal and sagittal slices, respectively, from wild-type and transgenic mice in an effort to model the transmission of these proteins [ 17 , 45 ].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, slice cultures have been employed to explore the prion-like propagation of Aβ and tau [ 42 , 43 , 44 ]. Recently, our group has explored the spreading of Aβ and α-Syn using organotypic coronal and sagittal slices, respectively, from wild-type and transgenic mice in an effort to model the transmission of these proteins [ 17 , 45 ].…”
Section: Introductionmentioning
confidence: 99%
“…Cells and synapses develop in a manner comparable to the in vivo environment [14]. This system allows direct and repeated manipulation, including the addition of exogenous compounds to the medium or application of collagen hydrogels to achieve a slow, localized protein or peptide release [15][16][17][18][19]. The absence of a blood-brain barrier permits direct investigation of the effects of toxic or therapeutic compounds [20].…”
Section: Study Of Ad-like Pathologies In Organotypic Brain Slicesmentioning
confidence: 99%
“…The prion hypothesis postulates systemic aggregation and propagation of Aβ and tau pathologies via interconnected pathways, akin to prion protein transmission [38][39][40][41][42]. Slice cultures have been used to study this pathology transmission [16,17]. Our prior research on postnatal WT animals showed increased spreading of P301S aggregated tau (aggTau) to the ventral areas of slices via neuroanatomically connected pathways [15].…”
Section: Use Of Exogenous Human Spreading On Mouse Brain Slicesmentioning
confidence: 99%
“…In addition, co-cultures of various brain regions including the nigrostriatal circuit ( 119 ), the cortex, and hippocampus ( 114 , 116 ), as well as entire sagittal and coronal organotypic cultures ( 120 ) have been reported, each of which can be used as a model for neurodegenerative disease. Recent work has shown that organotypic cultures can be prepared from aged mice, providing unique insight into aged neurons ( 121 ), and can be seeded with misfolded pathogenic proteins such as tau to study the propagation of misfolded protein throughout the tissue ( 122 ).…”
Section: Mouse Organotypic Culture Systemmentioning
confidence: 99%